2012
DOI: 10.4161/nucl.21055
|View full text |Cite
|
Sign up to set email alerts
|

A requirement for polymerized actin in DNA double-strand break repair

Abstract: Nuclear actin is involved in several nuclear processes from chromatin remodeling to transcription. Here we examined the requirement for actin polymerization in DNA double-strand break repair. Double-strand breaks are considered the most dangerous type of DNA lesion. Double-strand break repair consists of a complex set of events that are tightly regulated. Failure at any step can have catastrophic consequences such as genomic instability, oncogenesis or cell death. Many proteins involved in this repair process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 55 publications
(61 reference statements)
1
80
0
3
Order By: Relevance
“…pmRuby2, pmRuby2-TOX or pmRuby2-ΔHMG constructs were co-transfected into 3T3 cells with KU80-GFP or XRCC4-GFP using electroporation (Neon transfection system, Life Technologies). 8–24 h later, cells were treated with Hoescht 33342 and subjected to 405 nm laser-induced micro-irradiation and imaging as described previously (55). Images were processed and analyzed using Slidebook 5.0 software (Intelligent Imaging Innovations) and Adobe Photoshop CS6.…”
Section: Methodsmentioning
confidence: 99%
“…pmRuby2, pmRuby2-TOX or pmRuby2-ΔHMG constructs were co-transfected into 3T3 cells with KU80-GFP or XRCC4-GFP using electroporation (Neon transfection system, Life Technologies). 8–24 h later, cells were treated with Hoescht 33342 and subjected to 405 nm laser-induced micro-irradiation and imaging as described previously (55). Images were processed and analyzed using Slidebook 5.0 software (Intelligent Imaging Innovations) and Adobe Photoshop CS6.…”
Section: Methodsmentioning
confidence: 99%
“…5). Previous studies have shown polymerized actin is necessary for retention of Ku80 at sites of DNA damage (Andrin et al, 2012), and DNA damage has been shown to increase nuclear actin polymerization, potentially inducing formation of nuclear actin filaments that may play a role in nuclear oxidation (Belin et al, 2015) as well as the recruitment and activity of β-catenin (Yamazaki et al, 2016). Although we noted no evidence of nuclear actin filament formation, our study supports a model whereby recruitment of nuclear α-catenin stabilizes polymerized actin at sites of DNA damage (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…5). Polymerizing nuclear actin may act as a scaffold for other repair proteins at sites of DNA damage (Andrin et al, 2012), locally alter nuclear actin dynamics leading to downstream changes in transcription and chromatin remodeling (de Lanerolle and Serebryannyy, 2011;Serebryannyy et al, 2016a,b), or tether repair factories to the nuclear matrix and other nuclear subcompartments (Koehler and Hanawalt, 1996;Mahen et al, 2013;Marnef and Legube, 2017). Notably, lamins are known to regulate genomic stability as well as DNA damage repair (Gonzalo, 2014) and have been shown to interact with nuclear actin (Ho et al, 2013;Plessner et al, 2015;Simon et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This effect may delay p53 mediated apoptotic processes and allow DNA repair to be processed before apoptosis. Indeed, it has been reported that polymerized actin is required for DSB repair [141]. Binding of p53 to actin filaments is calcium dependent, and the interaction between these two entities is enhanced by DNA damage [142].…”
Section: Actin Dynamics Adf/cofilin and Ddrmentioning
confidence: 99%